Principles and practice of finite volume method - Adison, Haley, editor (New Jersey, NJ : Clanrye Intl., 2015)
The principles and practice of finite volume method are highlighted in this book. In this book, readers will find a subject which will increase their interest and involve them to further explore a challenge and work further on the presented solutions. This book can serve the purposes of both; a textbook and a practical guide. It presents a vast variety of ideas in FVM which is a result of the efforts of scientists from across the world. The major topics covered in this book are novel techniques and algorithms in FVM, solution of particular problems through FVM and application of FVM in medicine and engineering. This book is for anyone who wants to grow, improve and explore.